LEAD ACETATE INDUCED CHANGES IN OXYGEN CONSUMPTION OF FRESHWATER SNAIL BELLAMYA BENGALENSIS (LAMARCK) - KAMBALE, N.A.; NANAWARE, S.G. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2009)
The freshwater snails Bellamabengalensis (Lamarck) were collected from Rajararn tank, near Shivaji University, Koihapur. After acclimatization for a week, same sized healthy snails were subjected to mean LC50 value of lead acetate solution for 24 hrs., 48 hrs., 72 hrs. and 96 hrs intoxication. The dissolved oxygen for each time interval was estimated. The rate of oxygen consumption was measured in terms of mg/gm body weight/hrs/liter. With increase in intoxication period the rate of oxygen consumption was decreased. The oxygen consumption after 24 hrs.was decreased up to 26.25%. It was decreased up to 52.0 1% after 48 hrs., 73.08% after 72 hrs. and 81.76% after 96 hrs. The changes in oxygen consumption in the snails were discussed in relation to physiology of respiration under heavy metal stress environment.